Thematic tourism potential analysis of Bali Aga rural area, Buleleng, Bali - Nyoman Dini Andiani; I Made Antara; Ni Made Mas Yogiswari; Ni Ketut Arismayanti (Jurnal Pariwisata Pesona, 2023)
The thematic development of tourism in Bali Aga can be increased by maximizing the existing tourism potential in the National Priority Rural Area (KPPN), named Bali Aga. This article aims to determine the strengths, weaknesses, challenges and threats possessed by tourism potentials in Bali Aga, in order to maximize the potential for the development of tourism thematic priorities in Bali Aga. The method used in this research is descriptive qualitative method and SWOT analysis (Strength, Weakness, Opportunity, Threat). In addition, other methods used are observation, field studies, documentation and document studies. The results of the study show that the Bali Aga has strengths in terms of tourism potentials in the form of nature tourism and cultural tourism, its weaknesses are in the form of insufficient accessibility, as well as a bad image attached to the general public, the opportunities can be seen from the government involvement in this rural area development, and the threat is the the intense competition because the existence of other well-developed tourist villages. Therefore, it is very important to develop tourism thematic in Bali Aga to increase tourist arrivals and be able to compete with other rural areas in Indonesia.